Herbal Tea Production from Mimosa Pudica - N. P. Minh (Journal of Global Pharma Technology, 2016)
Drying is the most popular and basic method for post-harvest storage of herbs because it permits for the quick preservation of the herbal qualities of the herb material in a simple manner. Mimosa pudica is considered as a promising herbal candidate to undergo further exploration as evident from its pharmacological properties. Objective of this study focused on the effect of blanching temperature and time; oven drying temperature and storage condition to total phenolics (mg/g), total flavonoids (mg/g), ferric reducing/antioxidant power (FRAP or TE, mg/g), radical-scavenging activity DPPH (IC50, mg/mL) and sensory score of the dried Mimosa pudica tea. Results showed that Mimosa pudica should be blanched in hot water 95oC at 5 seconds in the present of citric acid 0.5% and then beeing dried by oven dryer at 50oC until 10.0% moisture. The final herbal tea could be preserved under vacuum in aluminum foil at 28oC to maintain flavonoid content for 12 months.Keywords: Blanching, Drying, Ferric reducing power, Flavonoids, Herbal, Mimosa pudica, Phenolics, radical-scavenging activity.